2017
DOI: 10.4049/jimmunol.1601462
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Peptidoglycan-Sensing Molecules NOD1 and NOD2 Promote CD8+ Thymocyte Selection

Abstract: Nucleotide-binding and oligomerization domain (NOD)-like receptors NOD1 and NOD2 are cytosolic innate immune receptors that recognize microbial peptidoglycans. Whilst studies have addressed the role of NOD proteins in innate immune responses, little attention has been given to their impact on the developing adaptive immune system. We have assessed the roles of NOD1 and NOD2 deficiency on T cell development in mice. Our results demonstrate that NOD1 and NOD2 promote the positive selection/maturation of CD8 SP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 71 publications
(79 reference statements)
2
16
0
Order By: Relevance
“…We would posit that the pleiotropic functions of Nod2 may be explained based on T cell-specific roles in antigen recognition vs. microbial sensing functions that help maintain balance between self-tolerance and host-defense mechanisms against infection, respectively. Our results are further supported by recent observations of similar discordant Nod2-Rip2 signaling functions in T cell responses; specifically, induction of c-Rel activity and induction of IL-2 to promote Th1 immunity 16 , CD8 + T cell development 32 , and CD69 expression and activation-induced cell death in response to alloantigen as is relevant to graft-versushost-disease 14 . Thus, our work complements other studies in which Rip2 also was found to be dispensable for T cell function 14,32,38,39 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We would posit that the pleiotropic functions of Nod2 may be explained based on T cell-specific roles in antigen recognition vs. microbial sensing functions that help maintain balance between self-tolerance and host-defense mechanisms against infection, respectively. Our results are further supported by recent observations of similar discordant Nod2-Rip2 signaling functions in T cell responses; specifically, induction of c-Rel activity and induction of IL-2 to promote Th1 immunity 16 , CD8 + T cell development 32 , and CD69 expression and activation-induced cell death in response to alloantigen as is relevant to graft-versushost-disease 14 . Thus, our work complements other studies in which Rip2 also was found to be dispensable for T cell function 14,32,38,39 .…”
Section: Discussionsupporting
confidence: 89%
“…5. After immunization of Rag1 −/− recipients, the transferred Rip2 −/− thymocytes (which have similar composition to WT mice 32 ) elicited significantly less severe uveitis compared to WT thymocytes ( Fig. 6c, d), indicating an inherent and opposing T cellular function for Rip2 in pathogenesis of uveitis.…”
Section: Resultsmentioning
confidence: 92%
“…More recent data show that both Nod1 and Nod2 promote CD8 single positive thymocyte-positive selection and Nod ligands can promote thymocyte maturation in culture (29), suggesting a T cell intrinsic role in thymocyte maturation events.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, while expression of Nod2 in the thymus has been known for some time 21 , it has thus far only been functionally linked to positive selection and maturation of CD8+ T cells by facilitating TCR-ERK signaling 70 . It has been previously reported that NOD2 controls the production of IL-23 by DCs via miR29, which directly regulated the transcription of Il12p40 and indirectly through Il23p19 18 .…”
Section: Discussionmentioning
confidence: 99%
“…S1b). Although the expression of Nod2 in thymic tissue has been known for some time 21 , the only functional role for NOD2 that has been described in the thymus has been in thymocyte selection 22 .…”
Section: Nod2 Negatively Regulates Thymus Regeneration By Suppressingmentioning
confidence: 99%